Surge Irrigation Reduces Irrigation Requirements for Soybean on Smectitic Clay‐Textured Soils. Issue 1 (17th August 2017) - Wood, C.W.; Krutz, L.J.; Falconer, L.; Pringle, H.C.; Henry, B.; Irby, T.; Orlowski, J.M.; Bryant, C. J.; Boykin, D.L.; Atwill, R.L.; Pickelmann, D.M.
Abstract : Core Ideas: Surge irrigation reduced the amount of water applied per irrigation event by 22% Surge irrigation reduced the total amount of seasonal irrigation water application by 24% Surge irrigation increased irrigation water use efficiency by 29% The Mississippi River Valley Alluvial Aquifer is declining precipitously due to irrigation withdrawal for row crop production. Currently, 25% of the soybean ( Glycine max L.) acres in the Mid‐South are planted on clay‐textured soils and furrow‐irrigated using conventional continuous flow (CONV), the least efficient irrigation delivery system. The objective of this research was to determine the effect of surge irrigation (SURGE) on amount of water applied, soybean grain yield, irrigation water use efficiency (IWUE), and net return above irrigation costs when implemented on clay‐textured soils. The research was conducted during the 2013 through 2015 growing seasons in Stoneville, MS and consisted of paired fields, with the same cultivar, soil texture, planting date, and management practices used on both sites. Paired fields were randomly assigned as SURGE or CONV. Water applied to each field was monitored with flowmeters, and irrigations were initiated based on soil moisture sensor thresholds. Relative to CONV, SURGE reduced the amount of water applied per irrigation event by 22% and total water applied in season by 24% ( P ≤ 0.0349). Soybean grain yield averaged 66 bu/acre and was not different between delivery systems ( P = 0.7711), but SURGE increased IWUE by 29% compared with CONV ( P = 0.0076). Net return above irrigation cost was not different between CONV and SURGE, regardless of diesel price or pumping depth ( P ≥ 0.1149). Results from this research indicate that soybean producers in the Mid‐South and other regions that irrigate using lay‐flat polyethylene tubing can adopt SURGE for soybean on clay‐textured soils without adversely affecting yield or on‐farm profitability while concurrently decreasing the demand on depleted groundwater resources.